A prospective comparative study of total extraperitoneal inguinal hernia repair: fixation versus without fixation of the mesh - Reddy S., Raghu Rami; Girish, T. U.; B. J., Sharath Chandra (International Surgery Journal, 2016)
Background:Mesh fixation during laparoscopic total extra-peritoneal (TEP) inguinal hernia repair is still controversial. Although many surgeons considered it necessary to fix the mesh, some published studies supported elimination of mesh fixation. Therefore, a randomized prospective comparative study was conducted in JSS Hospital to compare the postoperative pain, cost effectiveness and recurrence of fixation versus without fixation of mesh. Methods: A randomized prospective comparative study was carried out in 30 patients who underwent laparoscopic TEP inguinal hernia repair with (Group A) or without (Group B) fixation of the mesh. The postoperative pain scores are analyzed and compared by visual analogue scale at 24hrs, 1 week, and 1 month in both groups. The recurrence rate is analyzed and compared by follow up of patients after 6months in both groups. The cost effectiveness is compared in both groups in monetary terms. Results:Patients in whom the mesh was not fixed had less postoperative pain (median of VAS is 4 in group A and 2 in group B, p ≤ 0.0001), mean lesser cost of surgery (Rs. 13135 in group A and Rs. 9245 in group B, p≤ 0.0001). No hernia recurrences were observed in either group (follow up period of 6months). Conclusions:Elimination of fixation of mesh during TEP inguinal hernia repair significantly reduces the postoperative pain and cost of surgery and it does not lead to increased rate of recurrence.